Mapping Agro-Pastoral Infrastructure in the Post-Medieval Landscape of Maniot Settlements: The Case-Study of Agios Nikon (ex. Poliana), Messenia - Germanidou, Sophia (Journal of Greek Archaeology, 2018)
Mani is geographically defined as the middle of the three peninsulas of the Peloponnese at the southernmost part of Greece. Distinctive geographic features of the area are the predominance of Mount Taygetos, the absence of rivers, the rocky composition of the soil as we move south, and the concomitant limited expanse of arable land (Figure 1a). Nowadays, in terms of administration, it is divided into two units; the NW of the rather fertile Messenian (Outer) (Figure 1b) and the more rugged and barren SE Lakonian (Inner) Mani.